ANALISIS DASAR PERTIMBANGAN HAKIM TERHADAP PEMIDANAAN TINDAK PIDANA KORUPSI YANG DIPUTUS MINIMUM KHUSUS DI WILAYAH HUKUM PENGADILAN NEGERI PEKANBARU (Studi kasus Perkara No.40/Pid.Sus/Tipikor/2012/PN.PBR) - Sinaga, Manva Kusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Corruption is the enemy of every country in the world. Corruption is the misuse of duties and embezzlement of state funds or the company for personal gain or others. The impact of corruption can undermine the countrys economy, democracy and common prosperity. Failure to combat government corruption would further weaken the governments image in the eyes of society. One way for the eradication of Corruption Act is to impose criminal sanctions are firm and heavy to prosecute the perpetrators through the system correctly by the judge. The judge should have consider correct and proper under the law in the criminal verdict. The purpose of this script, that is : First, to determine the basic consideration in decisions criminal judge specific minimum on corruption cases which case No.40 / Pid.Sus / Tipikir / 2012 / PN.PBR. Second, to determine the impact of the imposition of the special minimum punishment of the accused and the perpetrators of corruption next.This type of research can be classified types of normative legal research, descriptive research, a study that illustrates clearly and in detail on the basis of consideration of the judge in imposing a special minimum punishment on Corruption, the source data used secondary data consisting of primary legal materials, secondary law, and tertiary legal materials, techniques of data collection in this study with the literature study method, after the data is collected and analyzed to conclude. From the results of research and discussion can be concluded that, first, the consideration of judges in imposing criminal sanctions minimum by using judgment juridical and non juridical. At the time of this verdict the judge considered to be true because according to the Law which adopts a special criminal with no minimum limit the duration of the prison were clearly outlines appropriate actions and the amount of loss that dikorupsikan. Second, the impact of the imposition of a minimum punishment for perpetrators of corruption that is the response to even eradicate Corruption will never be reached. This is because the decision is not able to create a deterrent to criminals and the attainment of the objectives of the theory of punishment itself. So from time to time the number of criminals is not decreased even more ways or modes is done in corruption.Keywords: Corruption - Criminal Special Minimum - Verdict Judge.